Revitalize Use Language English on Unit Education - Sam Hermansyah; Nasmilah Nasmilah; Abidin Pammu; Noer jjihad Saleh; Matteson Niva (Scientechno: Journal of Science and Technology, 2023)
This study aims at revitalizing the role of the English language in education, where it becomes the house of the students for most time in their lives. When something wrong happens and goes on the paradigm conformation of this revitalization, shifting assumptions should become one of the efforts and be strived by one of the most element who takes main responsibility on education itself – teacher. this study explores empirically and theoretically the teachers' paradigm on the use of English language in the real classroom. The participants were the teachers from private schools in Sidenreng Rappang joining a workshop due to Study Day Teachers conducted by the foundations. The workshop results were reflected and interpreted by the involvement of a related-literature reviews from previously researchers and experts - journal articles and scientific books.